META-ANALYSIS: THE GUIDED INQUIRY LEARNING MODELS EFFECT ON STUDENTS LEARNING OUTCOMES IN CHEMICAL LEARNING - Rindiany, Nindy Aprillia; Aini, Faizah Qurrata (Chimica Didactica Acta, 2024)
The guided inquiry learning model is an appropriate pedagogical approach for teaching chemistry, as it engages students directly in the learning process. The objective of this research was to analyze and determine the effect of the guided inquiry learning model on students' learning outcomes in chemistry. This research is a literature study that employs a meta-analysis approach, adapted from the PRISMA methodology. A total of 200 articles published on Google Scholar between 2020 and 2024 were collected using the Publish or Perish application with the keywords "the effect of guided inquiry model," "learning outcomes," and "chemistry." The screening process, which involved adhering to specific inclusion criteria, resulted in the identification of five articles. Subsequently, the ES value was calculated. The data analysis indicates that the guided inquiry model has the potential to enhance student learning outcomes in chemistry, with an average ES value of 1.42, which falls within the high category.